A two-phase composite materials approach to the workability of concrete - Topcu, İB.; Kocataşkin, F. (Elsevier BV, 1995)
Abstract The present article is an attempt to establish basic composition-property relations for fresh concrete, using the two-phase composite materials approach and the law of plastic viscosity. Results of common practical tests of unit weight, slump test and Vebe test on systematic fresh concrete series, performed by the authors, are presented and are expressed through the following analytical models: the simple mixture rule for the unit weight: δc = δm + (δa − δm) Va and the proposed plastic viscosity model for the workability tests: The slump test sc = sm 1 − M · V m 1 + k · V a + k′ · v a 2 The Vebe test Tm = Tm 1 + k · V a + k′ · V a 2 1 − M · V m with good agreement. The indices m, a and c refer to the mortar, the aggregate, and the concrete, respectively, and Va is the volume fraction of the coarse aggregate. The material constants M, k, and k′ depend on the characteristics of the mortar and the coarse aggregate phases. It is concluded that with the development of this analytical model a reasonable solution for the workability of fresh concrete has been obtained.